1978
DOI: 10.1002/aic.690240505
|View full text |Cite
|
Sign up to set email alerts
|

Influence of polymer additives on the gas‐liquid mass transfer in stirred tanks

Abstract: The influence of polymer additives upon the gas-liquid mass transfer in stirred tanks is examined. While the addition of sodium carboxymethylcellulose brings about a reduction of the overall liquid side mass transport coefficient which is in line with the predictions by earlier works, the reduction of kLa in polyacrylamide solutions of equal viscosity is much stronger. This is explained by the viscoelasticity of the PAA solutions, and an empirical correlation is proposed. SCOPERecent research has shown that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(30 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…It may be concluded that the exponent, m, in the relationship k L a L ∝µ −m for stirred tanks is between 0.35 and 0.6 based on the previously reported values of m of 0.4 by Yagi and Yoshida [4], 0.41 by Ranade and Ulbrecht [5], and 0.38 by Moo-Young and Kawase [32]. The value of n 1 of 0.37 in this study compares well with the findings of the papers mentioned above.…”
Section: May 2009mentioning
confidence: 81%
See 1 more Smart Citation
“…It may be concluded that the exponent, m, in the relationship k L a L ∝µ −m for stirred tanks is between 0.35 and 0.6 based on the previously reported values of m of 0.4 by Yagi and Yoshida [4], 0.41 by Ranade and Ulbrecht [5], and 0.38 by Moo-Young and Kawase [32]. The value of n 1 of 0.37 in this study compares well with the findings of the papers mentioned above.…”
Section: May 2009mentioning
confidence: 81%
“…As shown in Table 2, the values of A increased with increasing C s and decreasing d p , which means that the aqueous colloidal silica solution exhibits elastic behavior [5].…”
Section: Rheological Properties Of the Aqueous Colloidal Silica Solutionmentioning
confidence: 82%
“…Also, on the addition of agar to the saccharified food wastes medium (5.8 g/L), even the k L a value decreased to 10.7 hr −1 , but the viscosity and BC productivity were increased ( Table 2). It could be supposed that the BC productivity was increased due to the decreasing conversion rate of the cel − mutant by decreasing the shear stress and the prevention of BC coagulation due to the increased viscosity on the addition of a polysaccharides, such as agar [16,17]. As a result, it was concluded that the influence of the viscosity was higher than that of the k L a on the BC productivity.…”
Section: Influence Of K L a And Viscosity On Bc Productionmentioning
confidence: 99%
“…Deborah number, which was obtained from a power-law model [14] of the relationship between the measured shear stress and first normal stress difference against the shear rate of the aqueous nano-sized colloidal silica solution, was used to obtain a unified correlation between the values of k L a in water and that in aqueous nano-sized colloidal silica solutions. The absorption rates of CO 2 were measured in aqueous nano-sized colloidal silica solution with diisopropanolamine (DIPA) and were compared with those estimated by the mass transfer mechanism with chemical reaction based on the film theory.…”
Section: Introductionmentioning
confidence: 99%